Návrh dílčí části informačního systému - Karmazin, Alexandr (Vysoké učení technické v Brně. Fakulta podnikatelská, 2014)
Bakalářská práce se zaměřuje na sestavení návrhu informačního systému pro firmu, na základě analýzy současné stavu podniku a procesů v něm probíhajících. Výsledkem bude informační systém, který snižuje náklady a zvyšuje efektivitu práce v oblasti personalistiky.

This thesis focuses on the preparation of the draft information system for the company, based on analysis of the current status of the organization and the processes going on within it. The result will be an information system that reduces costs and increases efficiency in human resources.
Design of an Information System Part
Keywords: informační systém; IS; EPC; SWOT; PEST; information system; IS; EPC; SWOT; PEST